All-Polyethylene versus Metal-Backed Tibial Components in Total Knee Arthroplasty - AbuMoussa, Samuel; White, Charles Cody, IV; Eichinger, Josef K.; Friedman, Richard J. (The Journal of Knee Surgery, 2019)
All-polyethylene tibial (APT) implants were incorporated into the initial design of the first total knee arthroplasty (TKA) systems. Since then, a dynamic shift has taken place and metal-backed tibial (MBT) implants have become the gold standard in TKA. This has mostly been due to the theoretical advantages of intraoperative flexibility and improved biomechanics in addition to the heavy influence of device manufacturers. MBT implant comes not only with a higher cost but also with potential for complications such as osteolysis, backside wear, and thinning of the polyethylene insert, which were not previously seen with APT implant. The majority of studies comparing APT and MBT implants have shown no difference in clinical outcomes and survivorship. Newer studies from the past decade have begun highlighting the economic advantages of APT implant, especially in patients undergoing primary, uncomplicated TKA. Use of APT implants in younger patients and those with a body mass index > 35 has not been extensively studied, but the existing literature suggests the use of APT implant in these cohorts to be equally as acceptable. With modern implant design and instrumentation, rising utilization of TKA along with current and future economic strain on health care, the increased use of APT implant could result in massive savings without sacrificing positive patient outcomes.
Keywords: total Knee Arthroplasty; all-polyethylene tibia; metal-backed tibia